Applications of graphene-based composites in the anode of lithium-ion batteries - Liu, Zhiming; Tian, Yu; Wang, Peng; Zhang, Guoxin (Frontiers in Nanotechnology, 2022)
Limited by the disadvantages of low theoretical capacity, sluggish lithium ion deintercalation kinetics as well as inferior energy density, traditional graphite anode material has failed to meet the ever-increasing specific energy demand for lithium-ion battery technologies. Therefore, constructing high-efficiency and stable anodes is of great significance for the practical application of lithium-ion batteries. In response, graphene-based composite anodes have recently achieved much-enhanced electrochemical performance due to their unique two-dimensional cellular lattice structure, excellent electrical conductivity, high specific surface area and superior physicochemical stability. In this review, we start with the geometric and electronic properties of graphene, and then summarize the recent progresses of graphene preparation in terms of both methods and characteristics. Subsequently, we focus on the applications of various graphene based lithium-ion battery anodes and their inherent structure-activity relationships. Finally, the challenges and advisory guidelines for graphene composites are discussed. This review aims to provide a fresh perspective on structure optimization and performance modulation of graphene-based composites as lithium-ion battery anodes.